Uji Efektivitas Formulasi Sediaan Patch Ekstrak Daun Binahong (Anredera cordifolia (Tenore) Steenis) Sebagai Penyembuh Luka Sayat Pada Kelinci - Sukmawati; Safira, Anita; Marini; Herliningsih (Jurnal Medika Farmaka, 2024)
Introduction: A wound is a condition where tissue continuity is broken by trauma from sharp or blunt objects, temperature changes, chemicals, electricity, radiation, or animal bites. One of the plants used as a wound healer is binahong leaves (Anredera Cordifolia (Tenore) Steenis). In previous studies, screening tests have been carried out and the results state that binahong leaves contain alkaloid, flavonoid, saponin, steroid and triterpenoid compounds that can accelerate the wound healing process. The purpose of this study was to determine whether binahong leaf patches can be used as wound healers with extract concentrations of 35%, 40% and 45%. Method: experimental research method in the laboratory. Result: the results of the patch preparation effectiveness test in formula F0 = the incision wound takes a long time to dry and close, F1 = the wound closes very quickly, F2 = the wound closes quickly enough and F3 = the wound takes a while to close. Conclusion. Of the 4 formulas, F1 tends to be more effective as a wound healer.